Hydrogen Sulfide and Endoplasmic Reticulum Stress: A Potential Therapeutic Target for Central Nervous System Degeneration Diseases - Zhong, Huimin; Yu, Huan; Chen, Junjue; Sun, Jun; Guo, Lei; Huang, Ping; Zhong, Yisheng (Frontiers in Pharmacology, 2020)
There are three members of the endogenous gas transmitter family. The first two are nitric oxide and carbon monoxide, and the third newly added member is hydrogen sulfide (H2S). They all have similar functions: relaxing blood vessels, smoothing muscles and getting involved in the regulation of neuronal excitation, learning and memory. The cystathionine β-synthase (CBS), 3-mercaptopyruvate sulfur transferase acts together with cysteine aminotransferase (3-MST/CAT), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfur transferase with D-amino acid oxidase (3-MST/DAO) pathways are involved in the enzymatic production of H2S. More and more researches focus on the role of H2S in the central nervous system (CNS), and H2S plays a significant function in neuroprotection processes, regulating the function of the nervous system as a signaling molecule in the CNS. Endoplasmic reticulum stress (ERS) and protein misfolding in its mechanism are related to neurodegenerative diseases. H2S exhibits a wide variety of cytoprotective and physiological functions in the CNS degenerative diseases by regulating ERS. This review summarized on the neuroprotective effect of H2S for ERS played in several CNS diseases including Alzheimer’s disease, Parkinson’s disease and depression disorder, and discussed about the corresponding possible signaling pathways or mechanisms as well.